Social theory and the politics of higher education critical perspectives on institutional research - Murphy, Mark 1969-; Burke, Ciarán; Costa, Maria Cristina Castilho; Raaper, Rille (Social theory and methodology in education research, 2021)
"Bringing together an international group of scholars who shine a theoretical light on the politics of academic life and higher education, the book explores three key areas - institutional governance, academic work and student experience through a theoretical lens, using the ideas of Michel Foucault, Barbara Adams, Margaret Archer, Pierre Bourdieu, Norbert Elias and Donna Haraway, among others. Global case studies draw on a wide range of research approaches, and each chapter includes a set of critical reflections on how social theory and research methodology can work in tandem."